The Social Construction of Violence Among Adolescents and Young People in the Family, School and Community Environment and its Repercusions on Their Life Projects in The Area Known as Pedregales - Carbajal Belmont, Cecilia (Trabajo Social UNAM, 2016)
In everyday life, the social processes people undergo are continuously changing. In this regard, the processes involving the dynamics of social interrelations are changing every day until they become normal. Violence is one of these social practices since it is the dominance in participation of several actors, taking on different meanings, and these are taken up by subjects in daily life, perhaps because they have become imperceptible and are therefore confused with “ a means of accepting” of one subject to another. Violence is a growing, latent problem. Not that it did not exist before; many The Social Construction of Violence Among Adolescents and Young People in the Family, School and Community Environment and its Repercusions on Their Life Projects in The Area Known as Pedregales Cecilia Carbajal Belmont Social reality is complex and reflects the dynamics of the social interrelations of its subjects starting with the social processes which they exercise. In this sense, in order to carry out the present analysis we take as a starting point the supposition that social processes which are created as a product of a change in social interrelations produce breaks in these ties, generating a situation in which recognizing the other one has no meaning events in history make reference to the use of violence as a means of imposing power. However, the intention of the following reflection is to show how interaction based particularly on violence: harassment, illegality, stigmatization, among other factors, influences the inclusion of violence as a way of life and of socialization. It is not only a matter of adolescents and young people, but rather includes other actors and various environs. The social construction of violence involves the assimilation of behavior not just from the desk, classroom or schoolyard, but also from the heard of the family responsible not only for providing food, clothing and shelter, but also ethical and civic values and the concept of solidarity.